IMPLEMENTASI REST API PADA APLIKASI PELAYANAN EMERGENCY PUSKESMAS BERBASIS WEB DAN MOBILE - Alfandi Yahya Muhaimin; Adam Sekti Aji (Politeknik Bisnis Indonesia, 2023)
Bruno Community Health Center, is a health service facility located in Bruno. The aim is to provide first-class public health measures and individualized care for the local population. However, in the Bruno area there are still many villages that are far from the Community Health Center and there are limited four-wheeled transportation vehicles. This condition makes it difficult during emergency situations that can threaten a person's life, such as accidents or recurrence of serious illnesses such as heart disease that require immediate medical action. So a solution is needed for this problem. Therefore, from the results of this research, this research designs and builds a web and mobile-based emergency service ordering system which aims to make it easier for the public to order emergency services (ambulances) when an emergency occurs and there is also a consultation menu to provide convenience to the people who need it. will consult easily online. The method used in the research is the waterfall method. This system was built using a MySql database, and uses the Java programming language. The next step is to test it using the black box method. The test results show that the application is suitable for use.